ANALISIS KENDALA OPERASIONAL PADA KOMPRESOR SKG X MILIK PT. P PRABUMULIH PADA PERIODE APRIL 2018 – MARET 2019 - Azka Roby Antari; Zulfan Yusuf Asdan (Jurnal Cakrawala Ilmiah, 2023)
The gas compressor engine is the main equipment at the Gas Compressor Station (SKG). The working principle is gas compression, the compressor has rotating impeller blades pushing the gas into the diffuser forcing the gas to move into the vessel until the pressure on the gas increases. At SKG X PT. P Prabumulih who supplies gas to PT. Pusri, there are 4 compressor units (A, B, C, D), where in one day three compressor units are operating, and one compressor unit is in stand-by condition or under maintenance so it does not operate. The total operating hours of all compressors in one day is 72 hours and total stand-by hours are 24 hours. This quantitative research analyzes compressor performance data to obtain operational constraints experienced by compressors and their impact on compressor performance. Based on the results of the analysis, the hours of operation and stand-by of the 4 compressor units during a year did not run normally, due to some troubles with the compressor, a total of 25,773 working hours, 9,075 hours of standby, 444 hours of damage/loss. No compressor works 100% full, compressor B has the worst breakdown hours with 173 hours (3.64% of the total breakdown hours). During the year, there were 59 occurrences of damage to the compressor consisting of 26 types of damage with the peak performance decline occurring between June and July, which resulted in a loss of 2% of productive hours per year. This certainly has an impact on the loss of production target volume.